Exposure to PM10 as a risk factor for the development of nasal obstruction and chronic obstructive pulmonary disease. (January 2014) - Sichletidis, Lazaros; Spyratos, Dionisios; Tsiotsios, Anastasios; Haidich, Anna-Bettina; Chloros, Diamantis; Ganidis, Ioannis; Michailidis, Dimitrios; Triantafyllou, Georgios; Kottakis, George; Melas, Dimitrios
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: To investigate whether air pollution is a potential risk factor for airways obstruction. Methods: A prospective cohort study (11·3±2·9 years) that took place in two areas (Eordea where concentration of PM10 was high and Grevena, Greece). We used the MRC questionnaire, spirometry, and anterior rhinomanometry at both visits. Results: Initially we examined 3046 subjects. After excluding chronic obstructive pulmonary disease (COPD) patients, we re-examined 872 subjects and 168 of them had developed COPD (Grevena: 24·3%, Eordea: 18·5%). Multivariable logistic regression analysis showed that the area of residence and thus exposure to air pollution was not a risk factor for the development of COPD (OR: 0·51, 95% CI: 0·18–1·46, P = 0·21). On the other hand, residence in Eordea was strongly related to the development of severe nasal obstruction (OR: 11·47, 95% CI: 6·15–21·40, P<0·001). Similar results were found after excluding patients with COPD stage I as well as in the subgroup of never smokers. Conclusion: Air pollution was associated with severe nasal obstruction but not with COPD development.